GaN Schottky barrier diodes with nickel nitride anodes sputtered at different nitrogen partial pressure. (April 2019) - Li, Xiaobo; Pu, Taofei; Taiki, Hoshi; Zhang, Tong; Xie, Tian; Luke Fujiwara, Shigeki Joseph; Kitahata, Hiroshi; Li, Liuan; Kobayashi, Sachio; Ito, Motoo; Li, Xianjie; Ao, Jin-Ping
Abstract: Nickel nitride (Nix N) films were deposited by magnetron reactive sputtering under varying N2 partial pressure (P(N2 )) conditions range from 0.005 to 0.184 Pa. With the increasing P(N2 ), the deposition rate decreased while the resistivity and root mean square roughness increased. X-ray diffraction (XRD) and X-ray photoelectron spectra (XPS) indicate that Ni4 N and Ni3 N phases dominate the films at low and medium P(N2 ), respectively. In addition, Ni2 N phase can be also obtained at high P(N2 ). The Ni/N ratio evaluated from the energy dispersive X-ray spectrum is consistent with the Nix N phases showed in the XRD spectra of different P(N2 ). Compared with the GaN diodes with Ni anode, the Schottky barrier height and turn-on voltage of the Schottky barrier diodes with Nix N anode were increased by 0.03–0.18 eV and 0.03–0.15 V, respectively. Capacitance-voltage curves demonstrated that good interface quality with no obvious hysteresis was realized. Ni3 N anode diodes obtained at medium P(N2 ) possess a high barrier height and a low reverse leakage current are regarded as a promising anode material. Highlights: Nix N films were deposited by sputtering under P(N2 ) from 0.005 to 0.184 Pa. Ni4 N, Ni3 N and Ni2 N phases were observed and analyzed. SBH of the Nix N-GaN SBDs were 0.03–0.18 eV higher than Ni. Ni3 N was regarded as a promising anode material.